How the perceived effectiveness of a female coach is influenced by their apparent masculinity / femininity - Murraya, R.; Lord, R.; Lorimer, R. (The Sport Journal, 2020)
The aim of this study was to investigate how the apparent masculinity/femininity of a coach influenced others` perceptions of their ability to interact successfully with their athletes. Seventy-three participants (44 males, 29 females, Mage=23.8 SD= ± 8.41) watched four videos depicting a coach working with a group of athletes. Each video was the same but featured the four combinations of masculinised/feminised coach and male/female athletes. Participants rated the coach on perceived relationship quality, empathy, and competency. There was a main effect in relationship quality (closeness) and three of four subscales of coaching competency, with the masculinised coach rated higher than the feminised coach. There was also a non-significant trend for the feminised coach to score higher in relationship quality and competency when working with male athletes compared to female athletes, and the masculinised coach to score higher with females. For affective empathy, there was a main effect for athlete sex, with both coaches rated higher working with male athletes. There was also a non-significant trend for both coaches` cognitive empathy to be rated higher when working with male athletes. The perception of the masculinity/femininity of a coach influences how others understand their interactions even when the behaviors of that coach are similar across situations. Coaches need to be aware that gender-based stereotypes may influence how others perceive their competency. This could potentially affect coach effectiveness and career progression.